Surface Interaction Model for Great Thickness Masonry - Sánchez, Ariel; González del Solar, Gerardo A.; Martín, Pablo E.; Maldonado, Noemi G. (Frontiers in Built Environment, 2017)
At present, in the most important seismic zone of Argentina, many of the historic masonry structures present damages due to the actions to which they have been subjected but it is necessary to study the behavior of walls of ceramic masonry of great thickness. This work presents the comparison between the results obtained from the numerical simulation of ceramic masonry walls subjected to compression and shear strength, through the use interaction surfaces using commercial software ABAQUS, versus the data obtained from physical-mechanical tests performed in 1:1 scale on the laboratory of the CeReDeTeC. Tested walls were made with of solid masonry bricks with cement and lime mortar for 26 and 45 cm thick respectively. These are compared with the obtained results by the analysis software, considering mortar joints as interaction surfaces, trying to get the modeling that represents the behavior of the union of the elements mortar and masonry. The conclusions of the work, details strengths and weaknesses of this type of masonry modeling, and the desirability of developing models that allows the identification and analysis of the behavior of the weakest of the masonry element.